Assessment of Choroidal Vascularity and Choriocapillaris Blood Perfusion After Accommodation in Myopia, Emmetropia, and Hyperopia Groups Among Children - Chang, Xuejiao; Li, Mu; Lv, Liang; Yan, Xiaoqin; Liu, Ying; Zhu, Mengxia; Wang, Junming; Wang, Ping; Xiang, Yan (Frontiers in Physiology, 2022)
Purpose: To investigate choroidal vascularity (CV) and choriocapillaris blood perfusion before and after accommodation in myopia, emmetropia, and hyperopia groups among children. Methods: This study included 39 myopic eyes from 22 subjects, 17 emmetropic eyes from 11 subjects, and 18 hyperopic eyes from 10 subjects. All subjects were children. Choroidal thickness (CT) and CV, including total choroidal area (TCA), luminal area (LA), and stromal area (SA) were measured using swept-source optical coherence tomography (SS-OCT). Choriocapillaris luminal area (CLA) was measured using SS-OCT-angiography before and after accommodation (near reading with an additional –3 diopter lens). Results: For baseline results, except horizontal CV (showing no significant differences between myopia and emmetropia groups), both horizontal and vertical CT and CV were significantly smaller in the myopia group than in the emmetropia or hyperopia groups. In terms of CLA, no significant differences were observed among the myopia, emmetropia, and hyperopia groups. In addition, only myopic eyes showed significant decreases in CT and CV, whereas most CT and CV of emmetropic and hyperopic eyes showed non-significant decreases after accommodation. Furthermore, accommodation induced no significant changes in CLA in the myopia, emmetropia, or hyperopia groups. Conclusions: Myopia had thinner baseline choroid and lower baseline choroidal blood perfusion. Furthermore, myopic eyes were more prone to choroidal thinning and blood perfusion decreases after accommodation.